Nucleocytoplasmic p27Kip1 Export Is Required for ERK1/2-Mediated Reactive Astroglial Proliferation Following Status Epilepticus - Kim, Ji-Eun; Kang, Tae-Cheon (Frontiers in Cellular Neuroscience, 2018)
Reactive astrogliosis is a prominent and ubiquitous reaction of astrocytes to many types of brain injury. Up-regulation of GFAP expression and astroglial proliferation are hallmarks of reactive astrogliosis. However, the mechanisms that regulate reactive astrogliosis remain elusive. In the present study, status epilepticus (SE, a prolonged seizure activity) led to reactive astrogliosis showing the increases in GFAP expression and the number of proliferating astrocytes with prolonged extracellular signal receptor-activated kinases 1/2 (ERK1/2) activation and reduced nuclear p27Kip1 level. U0126, an ERK1/2 inhibitor, showed opposite effects. Leptomycin B (LMB), an inhibitor of chromosomal maintenance 1 (CRM1), attenuated nucleocytoplasmic p27Kip1 export and astroglial proliferation, although it up-regulated ERK1/2 phosphorylation and GFAP expression. Roscovitine ameliorated the reduced nuclear p27Kip1 level and astroglial proliferation without changed GFAP expression and ERK1/2 phosphorylation. U0126 aggravated SE-induced astroglial apoptosis in the molecular layer of the dentate gyrus that was unaffected by LMB and roscovitine. In addition, U0126 exacerbated SE-induced neuronal death, while LMB mitigated it. Roscovitine did not affect SE-induced neuronal death. The present data elucidate for the first time the roles of nucleocytoplasmic p27Kip1 transport in ERK1/2-mediated reactive astrogliosis independent of SE-induced neuronal death and astroglial apoptosis. Therefore, our findings suggest that nucleocytoplasmic p27Kip1 export may be required for ERK1/2-mediated astroglial proliferation during reactive astrogliosis, and that nuclear p27Kip1 entrapment may be a potential therapeutic strategy for anti-proliferation in reactive astrocytes.